Linkage of two distinct AT-rich minisatellites at multiple loci in the genome of Theileria parva - Bishop, Richard P.; Morzaria, S.P.; Gobright, E.I. (Elsevier, 1998)
Minisatellite tandem repeat elements are well known components of vertebrate genomes, but have not yet been extensively characterized in lower eukaryotes. We describe two unusual. AT-rich minisatellites of the protozoan parasite Theileria parva whose sequences are unrelated to the G/C-rich `chi minisatellite superfamily' of vertebrate and plant genomes. The T. parva tandem repeats, one with a conserved sequence T 2-5 ACACA (6-17 copies), and the other with a 6-bp core sequence of either ACTATA or TATACT associated with additional variable sequences in repeats of 10-17 bp (3-7 copies), were closely linked at more than 20 sites in the T. parva genome, separated by 390, 510 and 660 bp at three loci analysed in detail. Such linkage is without precedent in minisatellites so far analysed in other organisms. The minisatellite loci were widely dispersed on 13 out of 33 genomic SfiI fragments, on all four T. parva chromosomes and did not exhibit a telomeric bias in their distribution. Analysis of flanking sequences revealed no obvious conserved sequences between the five loci, or other multicopy repeat sequences outside the minisatellite regions. The T 2-5 ACACA minisatellite was highly effective as a multilocus fingerprinting probe for discrimination of T. parva isolates. Analysis of two individual minisatellite loci revealed variation between the genomic DNAs of two T. parva isolates in the copy number of the constituent repeats within the array, similar to that typical of vertebrate minisatellites.